The state of competition of the Turkish banking industry: An application of the Panzar‐Rosse model - Aktan, Bora; Masood, Omar (Journal of Business Economics and Management, 2010)
This paper examines the competitive structures of the Turkish banking industry over the period 1998–2008 and investigates the factors that can explain differences in the degree of competitiveness. The Panzar‐Rosse method is used to test for the competitive nature of the industry, which also gives the measure of competition, the H‐statistic, is related to a number of industry controls and prevailing banking structures. Our results indicate that the banking industry in Turkey is in an equilibrium state, further they are in long run equilibrium. We also found that the banks in Turkey are operating as a whole under conditions of monopolistic competition. However, the banks were able to achieve high records of profitability in monopolistically competitive markets. Konkurencija Turkijos bankininkystės sektoriuje: Panzar-Rosse modelio taikymas Santrauka. Straipsnyje tyrinėjamos konkuruojančios struktūros ir veiksniai, darantys įtaką skirtingam rinkos žaidėjų konkurencingumo laipsniui Turkijos bankininkystės sektoriuje 1998–2008 m. Bankininkystės sektoriaus konkurencijai įvertinti taikomas Panzar‐Rosse metodas. Rezultatai leidžia teigti, kad bankininkystės sektorius Turkijoje yra pusiausvyros būsenos, pereinančios į ilgalaikį etapą. Taip pat nustatyta, kad bankai Turkijoje veikia monopolinės konkurencijos ąalygomis. Šiomis sąlygomis Turkijos bankai sugebą pasiekti aukštapelningumą. Reikšminiai žodžiai: bankininkystės sektorius, banku konkurencija, Panzar‐Rosse metodas, pusiausvyros testas, Turkija. First Published Online: 14 Oct 2010